A high-profile police-involved shooting, civil unrest, and officers’ perceptions of legitimacy: insights from a natural experiment - Turchan, Brandon (Journal of experimental criminology, 2021)
To examine the effects of a high-profile police-involved shooting that resulted in a civil unrest on officers’ attitudes towards their communities and job performance., A natural experiment design and original data from a population survey of 1,003 police officers in Newark are used to compare officers’ perceptions of community support for law enforcement, the impact of repeated media scrutiny of law enforcement on their job, and officers' aversion to discipline before and after the civil unrest that occurred in response to the controversial police shooting of Keith Scott in Charlotte., In the weeks after the Keith Scott incident, officers reported significantly lower levels of perceived community support for law enforcement and greater discipline aversion, while no significant change in the impact of media scrutiny was observed., Findings suggest officers may not be immune to controversies involving police in other cities and might project onto the communities they police the feelings of hostility expressed towards law enforcement elsewhere.